Productivity and economics of mungbean as influenced by chemical weed control - Mirjha, Panch Ram; Prasad, S.K.; Singh, M.K.; Baghel, Pragati; Paikra, Ram Hari (Annals of Agricultural Research, 2014)
Short Note